2022
DOI: 10.5334/aogh.3529
|View full text |Cite
|
Sign up to set email alerts
|

Actions and Adaptations Implemented for Maternal, Newborn and Child Health Service Provision During the Early Phase of the COVID-19 Pandemic in Lagos, Nigeria: Qualitative Study of Health Facility Leaders

Abstract: Background:The early phase of the COVID-19 pandemic led to significant disruptions in provision of maternal, newborn, and child health (MNCH) services, especially in low-and middle-income countries (LMICs) with fragile health systems, such as Nigeria. Measures taken to 'flatten the curve' such as lockdowns, curfews, travel restrictions, and suspension of public services inadvertently led to significant disruptions in provision of essential health services. In these countries, health facility leaders are direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Evidence from Kenya, Maldives, Pakistan, and Sri Lanka revealed the availability of PPE being ensured in PHC facilities [ 24 , 28 , 45 48 ] to safeguard the continuity of health services [ 36 ]. The LMICS including Cameroon, Ethiopia, Maldives, Myanmar, Morocco, Nepal, Nigeria, South Africa, and Yemen documented measures to ensure the availability of essential medicines, equipment, and supplies at the facility level during the COVID-19 pandemic [ 24 , 28 , 31 , 34 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from Kenya, Maldives, Pakistan, and Sri Lanka revealed the availability of PPE being ensured in PHC facilities [ 24 , 28 , 45 48 ] to safeguard the continuity of health services [ 36 ]. The LMICS including Cameroon, Ethiopia, Maldives, Myanmar, Morocco, Nepal, Nigeria, South Africa, and Yemen documented measures to ensure the availability of essential medicines, equipment, and supplies at the facility level during the COVID-19 pandemic [ 24 , 28 , 31 , 34 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies were conducted during the COVID-19 pandemic attempting to maintain or enhance children’s vaccination. These studies suggested using innovative approaches may be useful strategies for the post-pandemic period, such as using utilizing online technologies to remind parents and update them parents about their children’s vaccination status and remind them about the vaccination schedule [ 67 , 68 , 69 ], providing phone counselling interventions for children’s vaccination in parents [ 70 ], using telemedicine to provide necessary health information to assist parents in achieving self-efficacy and making decisions for their children’s vaccination [ 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and using a chatbot real-time consultation messenger service to increase in parents’ motivation and self-efficacy to vaccinate their children [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leaders needed to apply a more transformational style of leadership which meant that they worked with staff to identify their needs and how best to support them while creating a vision to guide the change in approach to service delivery which was critically needed during the early part of the COVID-19 pandemic. Providing support for transportation, communication and feeding requirements during this time while managing the anxieties of the staff through use of personal direct phone calls, direct motivation, provision of the then hard-to-source PPE and psychological support classes were some of the strategies that health leaders used in Lagos (Balogun et al , 2022). However, while many HCWs were beneficiaries of some of these efforts, many issues and cause of anxieties remained unaddressed (Ameh et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, while many HCWs were beneficiaries of some of these efforts, many issues and cause of anxieties remained unaddressed (Ameh et al , 2021). Ultimately, the capacity of leaders to provide robust support to staff depends on the resources available to them and health leaders who were able to provide more robust support in Lagos were those that had been building capacity for such crisis pre-pandemic (Balogun et al , 2022). Moreover, it has been widely reported that health systems in Africa were inadequately prepared for the pandemic (Tessema et al , 2021).…”
Section: Discussionmentioning
confidence: 99%